PENGARUH PEMBERIAN EKSTRAK SECANG (Caesalpinnia sappan L.) TERHADAP KUALITAS SENSORIS DAN MIKROBIOLOGIS KUE BOLU KUKUS TAHUN 2014 - Riezky Aulia Yulandani; Martha Irene Kartasurya; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Cases of food-borne diseases are still quite high in the community. The cause of most cases were related to microbes. Sappan is one of the natural dyes, which also has an antibacterial effect. The purpose of this study was to analyze the effect of sappan wood extract to sensorial and microbiological quality of steamed cake. This research is a true experimental study with post-test only control group design. Sensorial quality was measured with a hedonic test, which was performed on 9 panelists who were given 4 groups of steamed cake contain 1%, 2%, 3% of sappan extract and steamed cake given food coloring. The number of bacteria was measured by total plate count test. Samples of microbiological quality test were 3 groups of steamed cake containing 1%, 2%, 3% of sappan extract with 9 replicates and control group without sappan extract. Sensorial quality test results showed no difference in the degree of acceptance of the panelists on the flavor (p=0.652) and taste (p=0.172). There were differences in the degree of acceptance of panelists to color (p=0.012), in which concentration of 2% and 3% were unlike. Microbiological test results showed that Staphylococcus aureus was not found for 4 days of observations both on sample with extract sappan or not but Escherichia coli and Streptococcus pneumoniae were found on the second day of observation on the whole samples. It is concluded that sappan extract on steamed cake did not affect the acceptance of the flavor and taste but affected on the acceptance of color. Sappan extract at a concentration of 3% could not inhibit the growth of Escherichia coli and Streptococcus pneumoniae.